Human System Modeling for Optimum Labor Utilization and Man-Machine Configuration - Abdullah, Rohana; Abd Rahman, Md Nizam; Khalil, S.N. (International Journals of Engineering and Sciences, 2014)
Manufacturing organization with increased in the organizational complexity, is facing difficulty in measuring its performance. Various factors could affect manufacturing performance such as equipment performance, material planning and human resources. In this paper, focus was given primarily on the human resource which was considered as an important factor of the simulation model development to achieve optimum utilization and ensure efficient operator allocation to the machines. Static modeling was performed to capture all the critical factors contributing to the work such as the operator activity sequence, the time value for each activity and also the machine process time for each batch of product. A dynamic model was then developed to enable quantitative analysis in the optimization of human system performance. This paper illustrates the application of different modeling approaches to demonstrate advantages gained in the process of evaluating human system performance.